Relationship between the importance of technical and vocational education and training (TVET) programmes and its contributions towards sustainability of society’s development among Kuala Lumpur technical secondary students - Thevathas, Venutini; Zakaria, Anis (Human Resource Management Academic Research Society, 2024)
In the context of rapid technological change and the pressing need for sustainable development, the role of Technical and Vocational Education and Training (TVET) has gained increasing importance. However, the specific contributions of TVET programs to the sustainability of societal development, particularly among technical secondary students in Kuala Lumpur, remain underexplored. This study explores the relationship between the importance of Technical and Vocational Education and Training (TVET) programs and their contributions to the sustainability of society's development among secondary students in Kuala Lumpur, Malaysia. The objectives include assessing the importance and contributions of TVET for technical secondary students, determining the level of sustainability in TVET, and establishing the relationship between the importance of TVET programs and their contributions to societal development. This quantitative survey involved 105 students from Sekolah Menengah Teknik Kuala Lumpur. The instrument was adapted from (Igberaharha, 2021; Mahaputra, 2017; Hamdan et al., 2020). The study reveals a statistically significant correlation with the acceptance of perceptions, as the p-value is less than 0.001. In addition, the coefficient associated with this correlation is 0.532, indicating that the observed relationship has a moderate positive effect size. The findings underscore the importance of understanding and positively influencing students' perceptions to enhance the effectiveness and impact of TVET programs in fostering sustainable societal development.